Stealing Knowledge in a Landscape of Learning: Conceptualizations of Jazz Education. Issue 3 (8th July 2016) - Bjerstedt, Sven
Abstract : Theoretical approaches to learning in practice-based jazz improvisation contexts include situated learning and ecological perspectives. This article focuses on how interest-driven, self-sustaining jazz learning activities can be matched against the concepts of stolen knowledge (Brown & Duguid, 1996 ) and landscape of learning (Bjerstedt, 2014 ). Based on an extensive interview study with Swedish professional jazz musicians, it argues that the multidirectedness involved in jazz improvisational practice calls for a rich learning ecology framework including several didactic loci.